Willingness to pay for private and public improvements of vulnerable road users' safety - Linda Andersson Järnberg; Daniela Andrén; Lars Hultkrantz; E.Elisabet Rutström; Elin Vimefall (Örebro University School of Business, 2021)
A frequent finding in the empirical literature on cost-benefit analysis of traffic safety measures is that valuations of public goods are lower than valuations of private goods, contrary to theory predictions. This study elicits the willingness to pay for publicly and privately provided safety improvement benefiting cyclists and pedestrians, a relatively neglected group in this literature. Our results suggest that there is no significant difference between valuations of a private good and three versions of a public good as long as the good itself is the same, in our case a mobile phone app. The public good versions differ in attributes such as mandatory or voluntary use and private or public provision institutions. . This finding is consistent with the simultaneous presence of both financial altruism and safety altruism, or neither. Public institutions are preferred to private ones in the provision of the public goods, and voluntary participation is preferred to mandated regulation. We also find evidence that attitudes that favor using taxes to fund traffic safety projects, and public responsibility for traffic safety are associated with a higher willingness to pay.
Keywords: D60; O18; R41; 330; willingness to pay; public goods; infrastructure; cyclists and pedestrians; interval regression